1983
DOI: 10.1192/bjp.142.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Suppression Test in Depression and other Psychiatric Illness

Abstract: The prevalence of an abnormal response to the dexamethasone suppression test (DST) was examined in 119 in-patients suffering from a major depressive disorder and in 79 normal controls. Only 11 per cent of controls showed an abnormal DST as against 70 per cent of depressed patients. The specificity of the DST was examined by testing patients with other psychiatric disorders. Abnormal responses were found in one-fifth of a sample of schizophrenics, over one-quarter of abstinent alcoholics, two-fifths of neurotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
1
5

Year Published

1983
1983
1994
1994

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(61 citation statements)
references
References 11 publications
4
51
1
5
Order By: Relevance
“…On the other hand, Dewan [7] reported that 6 of the 20 (30%) schizophrenic patients were nonsuppressors. Coppen et al [8] reported that 10 of the 46 schizophrenic patients exhibited an abnormal DST response. There was one nonsuppressor among 9 schizophrenic patients in the study of Arana et al [9].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Dewan [7] reported that 6 of the 20 (30%) schizophrenic patients were nonsuppressors. Coppen et al [8] reported that 10 of the 46 schizophrenic patients exhibited an abnormal DST response. There was one nonsuppressor among 9 schizophrenic patients in the study of Arana et al [9].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to suppress plasma cortisol with the 1-mg dexamethasone suppression test (DST) has repeatedly been reported in major depressed patients [Carroll, 1980[Carroll, , 1982Brown and Shuey, 1980;Coppen et al, 1983;Feinberg and Carroll, 1984;Maes et al, 1986aMaes et al, , 1989a, Several studies showed that the DST may help con firm the diagnosis of major depression and distinguish that disorder from normal controls [Carroll et al, 1981] or from minor dépressives [Maes et al, 1986a[Maes et al, , 1989a. The postdexamethasone cortisol values at 8 a.m., 4 p.m. and 11 p.m. in parallel (anyone of the values showing nonsuppression) [Brown and Shuey, 1980;Carroll et al, 1981;Syvalahti, 1985] or the cortisol values at 4 p.m. only [Giles and Rush, 1982;Klein et al, 1984] at a threshold value 5= 5 pg/dl were recommended for this value of the DST for melancholia was not affected by the purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Moroji [5] reported that the diurnal variation of plasma 17-hydroxycorticosteroid (17-OHCS) is irregular and in dependent of emotion in chronic schizophrenics. Recent ly, Coppcn [6] found that the majority of nonsuppressors in DST among chronic schizophrenics had prominent negative symptoms such as affective flattening, poverty of speech and loss of drive. Coppen [7] also supported the association between DST nonsuppression and type II schizophrenia proposed by Crow [8], Crow [8] speculated that the negative symptoms observed in type II schizo phrenics may be due to structural abnormalities in the brain.…”
mentioning
confidence: 99%